Milestones in Personalized Medicine in Pemphigus and Pemphigoid - Bieber, Katja; Kridin, Khalaf; Emtenani, Shirin; Boch, Katharina; Schmidt, Enno; Ludwig, Ralf J. (Frontiers in Immunology, 2021)
Pemphigus and pemphigoid diseases are autoimmune bullous diseases characterized and caused by autoantibodies targeting adhesion molecules in the skin and/or mucous membranes. Personalized medicine is a new medical model that separates patients into different groups and aims to tailor medical decisions, practices, and interventions based on the individual patient`s predicted response or risk factors. The first application of personalized medicine was introduced into the field of autoimmune bullous diseases in 1953 when pemphigus and pemphigoid were distinguished by clinical and histological features. Not until approximately 30 years later, the next important milestones in personalized medicine in pemphigus and pemphigoid were made: the proof of the autoimmune pathogenesis, as well as the identification and cloning of several pemphigus/pemphigoid autoantigens. The latter has become the basis of the current, molecular-based diagnosis that allows the differentiation of about a dozen pemphigus and pemphigoid entities. The importance of autoantigen-identification in pemphigus/pemphigoid is further highlighted by the emergence of autoantigen-specific B cell depleting strategies. To achieve this goal, the chimeric antigen receptor (CAR) T cell technology, that is used for the treatment of certain hematological malignancies, was adopted, by generating chimeric autoantigen receptor (CAAR) T cells. In addition to these more basic science-driven milestones in personalized medicine in pemphigus and pemphigoid, careful clinical observation and epidemiology are again contributing to personalized medicine. The identification of clearly distinct clinical phenotypes in pemphigoid like the non-inflammatory and gliptin-associated bullous pemphigoid embodies a prominent instance of the latter. We here review these exciting developments in basic, translational, clinical and epidemiological research in pemphigus and pemphigoid. Overall, we hereby aim to attract more researchers and clinicians to this highly interesting and dynamic field of research.